Nutrition for the female athlete - Clark, Kristine; American College of Sports Medicine (Monterey, CA : American College of Sports Medicine, 2006)
Presents a comprehensive overview of the nutritional issues that physically active women face. Details the macronutrient and micronutrient needs of women athletes and offers several practical suggestions on how physically active women can effectively deal with their nutritional demands
Title from title screen
Presenter : Kristine Clark
Keywords: Women athletes -- Nutrition; Women athletes